How do you solve 43= - 5( y + 11) + 7y?

1 Answer
Sep 21, 2017

y=49

Explanation:

First we switch sides from
43=-5(y+11)+7y to -5(y+11)+7y=.
We will remove the 7y and the 43= and focus on the rest.
We will distribute parentheses/brackets using:
a(b+c)=ab+ac.

a would be -5, b would be y and c would be 11 in this case.

Using a(b+c)=ab+ac, we know that -5*y-5*11. Multiply -5*y=-5y and 5*11=55. Therefore the equation would be (with the 7y) -5y-55+7y.

Next, we group like terms: -5y+7y-55, and then add -5y+7y=2y.
The whole equation will then be 2y-55=43. Add 55 to both sides:

2y-55color(blue)+color(blue)55=43color(blue)+color(blue)55 and simplify it to be 2y=98.
Divide both sides by 2 and you get y=49.